Synthesis and Characterization of Fluoridated Silver Nanoparticles and Their Potential as a Non-Staining Anti-Caries Agent - Iris Xiaoxue Yin; Irene Shuping Zhao; May Lei Mei; Edward Chin Man Lo; Jinyao Tang; Quanli Li; Lok Yan So; Chun Hung Chu (2020)
Objectives: The first objective of this study was to prepare sodium fluoride (NaF) solution with various concentrations of polyethylene glycol-coated silver nanoparticles (PEG-AgNPs). The second objective was to study the antibacterial activity against Streptococcus mutans and the tooth-staining effect of the solution. Methods: PEG-AgNPs were prepared via the one-step chemical reduction of silver acetate with thiolated polyethylene glycol. The PEG-AgNPs were characterized with ultraviolet-visible spectrometry and transmission electron microscopy. The half maximal inhibitory concentration (IC50) for the PEG-AgNPs against Streptococcus mutans and human gingival fibroblasts (HGF-1) were determined. The staining effect on dentin and enamel for the 2.5% NaF solutions with PEG-AgNPs at 12,800, 6400, 1600, and 400 ppm was investigated using digital spectrophotometry. The IC50 of the fluoridated silver nanoparticles against Streptococcus mutans were measured. Results: The PEG-AgNPs have an average diameter of 2.56± 0.43 nm and showed excellent stability at high ionic strength (2.5% NaF) for 18 months. The IC50 of PEG-AgNPs against Streptococcus mutans was found to be 21.16± 1.08 ppm silver, which was half of IC50 against HGF-1 cells (42.36± 1.12 ppm), providing a working range to kill bacteria with no harm to human cells. The formulations with different concentrations of PEG-AgNPs showed no significant staining of teeth. Combining PEG-AgNPs with NaF significantly expanded the therapeutic window against Streptococcus mutans by reducing its IC50. Conclusion: A biocompatible solution of NaF with PEG-AgNPs was developed. Because it has antibacterial activity against Streptococcus mutans and no tooth-staining effect, it can be used as an anti-caries agent. Keywords: silver, nanoparticles, fluoride, dentin, caries, antibacterial